Một số biện pháp dạy học nói và nghe văn nghị luận xã hội cho học sinh lớp 10 - Lã , Phương Thúy; Trần , Thị Dung (Tạp chí Giáo dục, 2023)
The General Education Curriculum in for Literature issued by Vietnam Ministry of Education and Training in 2018 pays special attention to training communication skills (reading, writing, speaking, and listening) for students. In fact, there have been many research works on effective methods to teach reading and writing, despite a limited amount of research on teaching speaking and listening. Therefore, the article proposes some measures to promote the effectiveness of teaching Vietnamese speaking and listening skills within the subject of Literature. Specifically, the study suggests the use of debate activities and information technology in teaching social argumentative speaking and listening skills for 10th graders to promote learners’ linguistic and communicative competencies for students. Besides, developing speaking and listening skills also means enhancing their proactiveness, initiative and creativity in learning.